Synergy effect modelling of cavitation and hard particle erosion: implementation and validation (2021)
The prediction of the wear behaviour of components under conditions of cavitation and hard particle erosion requires the implementation of a new model capable of accounting for the accelerated damage due to the synergic effect of both phenomena. In a previous research, several simulations were performed to investigate why the damage on a surface is increased when a particle interacts with a collapsing bubble. Then those simulations were modified to develop a predictive equation that estimates the impact velocity of a particle when it is trapped by the microjet of a collapsing bubble near a solid wall. Subsequently, through the implementation in a computational fluid dynamics (CFD) software, the obtained expression is combined with the traditional Grant and Tabakoff hard particle erosion model for AISI 304 steel to develop a new model capable of predicting the synergic effect of cavitation damage and hard particle erosion. This new model is used in CFD simulations to calibrate and validate the predicted erosion rate with experimental results obtained using a slurry pot erosion tester under two conditions of particle concentration and two conditions of particle size combined with four triangular cavitation inducers that produced different cavitation conditions. Good agreement was found between the experimental and the predicted results using the developed model